2010
DOI: 10.1242/jcs.063107
|View full text |Cite
|
Sign up to set email alerts
|

AC. eleganseIF4E-family member upregulates translation at elevated temperatures of mRNAs encoding MSH-5 and other meiotic crossover proteins

Abstract: SummaryCaenorhabditis elegans expresses five family members of the translation initiation factor eIF4E whose individual physiological roles are only partially understood. We report a specific role for IFE-2 in a conserved temperature-sensitive meiotic process. ife-2 deletion mutants have severe temperature-sensitive chromosome-segregation defects. Mutant germ cells contain the normal six bivalents at diakinesis at 20°C but 12 univalents at 25°C, indicating a defect in crossover formation. Analysis of chromosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
53
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 59 publications
2
53
0
Order By: Relevance
“…IFE-2 has an even more de fi ned role. It regulates meiosis in hermaphrodites, because ife-2 mutants display severe chromosome segregation defects at elevated temperature (Song et al 2010 ) . Both factors have in common that they are important for ef fi cient translation of speci fi c mRNA subsets.…”
Section: Cap-mediated Regulationmentioning
confidence: 99%
“…IFE-2 has an even more de fi ned role. It regulates meiosis in hermaphrodites, because ife-2 mutants display severe chromosome segregation defects at elevated temperature (Song et al 2010 ) . Both factors have in common that they are important for ef fi cient translation of speci fi c mRNA subsets.…”
Section: Cap-mediated Regulationmentioning
confidence: 99%
“…This suggests that a ubiquitous eIF4E isoform might carry out global translation initiation, whereas the other isoforms might be involved in more specific processes of translation (Hernández and VazquezPianzola, 2005). Work in C. elegans supports this, as IFE-1, a germline-specific eIF4E, is required for sperm (Amiri et al, 2001;Kawasaki et al, 2011) and oocyte (Henderson et al, 2009) maturation, loss of IFE-2 affects chromosome segregation at meiosis (Song et al, 2010), and IFE-4 is involved in translating only a small set of neural and muscle mRNAs involved in egg laying (Dinkova et al, 2005).…”
Section: Introductionmentioning
confidence: 96%
“…Work in other organisms also supports functions for alternative forms of eIF4E and eIF4G in the germline. It is noteworthy that IFE-2, an alternative eIF4E in C. elegans, has, like Drosophila eIF4E-3, been linked to chromosome segregation at meiosis (Song et al, 2010). This degree of evolutionary conservation suggests an ancient translational mechanism for control of this process in sperm development.…”
mentioning
confidence: 99%
“…Five isoforms of eIF4E (IFE-1-IFE-5) are expressed in the nematode C. elegans (Jankowska- Anyszka et al, 1998;Keiper et al, 2000). We have previously shown that individual isoforms regulate a unique subset of mRNAs in a tissue-specific manner (Amiri et al, 2001;Dinkova et al, 2005;Henderson et al, 2009;Kawasaki et al, 2011;Song et al, 2010). Given that all IFEs bind to mRNA caps, these findings suggest a selective cap-dependent regulation that goes beyond mTOR regulation.…”
Section: Introductionmentioning
confidence: 99%